2017
DOI: 10.1159/000470846
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of an Internet-Based Imagery Rehearsal Intervention: A Randomized Controlled Trial

Abstract: Background: Nightmares are extremely dysphoric dreams, which are prevalent and associated with psychological strain. This study investigated (a) the efficacy of an internet-based imagery rehearsal therapy (IRT), (b) the role of imagery rescription, and (c) the role of guidance during internet-based IRT. Methods: A total of 127 patients suffering from mainly idiopathic nightmares were randomly assigned to 1 of 2 IRT internet-based groups (guided IRT; unguided IRT) or to 1 of 2 active control groups (frequency c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 36 publications
2
15
0
1
Order By: Relevance
“…Our findings raise the issue of whether the effectiveness of a blended care approach could be further enhanced by integrating it more into the inpatient program. Furthermore, since the effect of guidance on the efficacy of internet-based interventions is still controversially discussed [56], our study would have benefitted from a subgroup of participants with therapeutic guidance to explore the effect of therapeutic interventions. Finally, we are aware that we compared treatment packages with multiple effective ingredients [57] and that we could not control how Deprexis was supported by the different members of the staff.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings raise the issue of whether the effectiveness of a blended care approach could be further enhanced by integrating it more into the inpatient program. Furthermore, since the effect of guidance on the efficacy of internet-based interventions is still controversially discussed [56], our study would have benefitted from a subgroup of participants with therapeutic guidance to explore the effect of therapeutic interventions. Finally, we are aware that we compared treatment packages with multiple effective ingredients [57] and that we could not control how Deprexis was supported by the different members of the staff.…”
Section: Discussionmentioning
confidence: 99%
“…Because IRT is most often offered in a multicomponent treatment package, specific treatment mechanisms are difficult to identify: nightmare modification rarely occurs without any exposure to the aversive nightmare content (Lancee, Van Den Bout, & Spoormaker, ) and most treatment manuals also include psycho‐education, the keeping of sleep diaries, relaxation exercises and imagination techniques taken from the treatment of PTSD. Attempts to identify such treatment components have demonstrated that the simple recording of nightmares in a diary decreases nightmare frequency and nightmare distress (Lancee et al., ; Neidhardt, Krakow, Kellner, & Pathak, ); nonetheless, IRT as an adjunct therapy outperformed a comparison treatment that also included diaries (Gieselmann et al., ; Van Schagen et al., ). On the other hand, keeping detailed narrative sleep diaries was as effective as IRT (with the diaries) in decreasing nightmare frequency, whereas IRT outperformed detailed diaries in reducing nightmare distress.…”
Section: The Treatment Of Nightmare Disordermentioning
confidence: 99%
“…In the attempt to improve access to treatment, low‐threshold interventions such as telephone counselling (Schredl et al., ), Internet‐based applications and self‐help approaches (Gieselmann et al., ; Lancee et al., ) should be further developed and offered to the general public. There is an abundance of evidence that Internet‐based treatment is effective, with effect sizes comparable to those of face‐to‐face treatments; such novel approaches may help with disseminating, simplifying and, perhaps, increasing the effects of treatments (Andersson, Cuijpers, Carlbring, Riper, & Hedman, ; Cuijpers, Kleiboer, Karyotaki, & Riper, ).…”
Section: Future Perspectivesmentioning
confidence: 99%
See 2 more Smart Citations